GOVERNANCE BESED ON HONESTY ACCORDING TO THE PRINCIPLES OF GOOD GOVERNANCE ON TRANSPARENCY OF SUB-DISTRICT ADMINISTRATIVE ORGANIZATIONS IN PHU KHIAO DISTRICT, CHAIYAPHUM PROVINCE - Juntasaro (Moohuana), Phra Sittirak; Mamuangt, Phaitoon; Surapanyo, Phramaha Narin (Journal of MCU Nakhondhat, 2023)
The objectives of this research were 1) to study the level of governance based on transparency in good governance 2) to compare the levels of governance based on transparency in good governance 3) presenting the administration based on good faith according to the principles of good governance in terms of transparency of sub-district administrative organizations in Phu Khieo District Chaiyaphum Province the research methodology is an integrated research. The integrated research method is quantitative research by distributing questionnaires to a sample of 234 people from the personnel of the sub-district administrative organization. A total of 552 people and qualitative research by means of in-depth interviews from key informants, namely 1) 2 monks 2) 2 academics in political science 3) 5 leaders of sub-district administrative organizations, totaling 9 figures or people The results showed that 1) physical integrity have human relations with people who come in contact with sincerity. Are ready to serve, have sacrifices for the benefit of the people. Rule the people without seeking benefits in return develop oneself as a person with competence and expertise in governing with righteousness and righteousness and living on the principles of Dharma. Perform duties consistently, and have a good sense of society, be a moral person have good behavior in body, speech and mind, have a gentle manner, and humble, not disparaging the people. 3) Conscience Maintain honesty in work, with determination, not dishonest in duty that, they have been entrusted with pleasure in their responsibilities, be a moral person behave in good physical, verbal and mental manners, strictly supervise in administration, not violate moral principles and be a good example to society. When there was a problem in government, he solved the problem with due diligence until it was successfully accomplished.